2013
DOI: 10.1089/vim.2012.0043
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Isolated HCV Strains from Tunisian Hemodialysis Patients

Abstract: The present study describes the strains of hepatitis C virus (HCV) isolated from Tunisian hemodialysis patients. Thirty-three HCV strains isolated from different dialysis centers in Tunis City were amplified by RT-PCR in a region of the NS5b gene, genotyped by sequencing, and compared to international sequences by phylogenetic analysis. The phylogenetic tree showed that 16 HCV isolates have been identified as subtype 4k (48.5%), 7 as unspecified HCV-4 subtype (21.2%), 5 as subtype 4a et 1b (each 15.2%). The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…After removal of 187 duplicates, 382 irrelevant titles, and 81 papers with irrelevant abstracts, finally, 14 studies were eligible to be assessed in phylogenetic analyses (33-43, 50-52). In total, 505 sequences of HCV-1a and -1b were obtained from these 14 studies.…”
Section: Resultsmentioning
confidence: 99%
“…After removal of 187 duplicates, 382 irrelevant titles, and 81 papers with irrelevant abstracts, finally, 14 studies were eligible to be assessed in phylogenetic analyses (33-43, 50-52). In total, 505 sequences of HCV-1a and -1b were obtained from these 14 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, HCV genotypes 4, 5, and 6 are endemic to specific geographical areas: HCV-4 is mainly found in Egypt and Sub-Saharan Africa, HCV-5 in South Africa [5], and HCV-6 in South China and South-East Asian countries [28,40]. In Tunisia, previous epidemiological and phylogenetic studies, conducted on both healthy and HCV-infected subjects, reported a large predominance of genotype 1b [15,16,22]. Interestingly, our present results are in a prefect correlation with this data.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is important to consider HCV RNA measurement in these patients because the immunosuppression inherent to chronic renal disease, as a preventive factor against nosocomial spread of HCV [13]. Hemodialysis is considered one of the main risk factors of HCV infection, due to several invasive medical procedures and potential nosocomial transmission that patients with chronicrenal failure (CRF) are continuously submitted [13,22]. Furthermore, nosocomial transmission in the dialysis units may be associated with hemodialysis procedures, such as aerosol formation during fistula cannulation for vein access, accidents with contaminated blood, and direct contact with contaminated materials used by infected patients [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, HCV epidemic subtypes show high prevalence, low genetic diversity, and spreading during the 20 th century via blood transfusions, injecting drug use and invasive medical procedures. On the contrary, endemic subtypes reveal long persistence in human populations in geographically restricted areas, with low transmission rates and a high genetic diversity as a result [ 36 - 38 ].…”
Section: Phylogenetic Analysismentioning
confidence: 99%